KRIYA TAPESTRI DENGAN OBJEK SEMUT - LIA MITA SARI, Drs. Erwin A, M.Sn., Dra. Zubaidah, M.Pd. (Universitas Negeri Padang, 2019)
This final work aims to visualize the shape and life of ants in tapestry work. The uniqueness and idiosyncrasy of ants teaches humans the unyielding nature without despair facing all obstacles. In this work two techniques are used, namely the technique of soumak, and the technique of the giordes. The method of the process of creating this work is: the stages of preparation, elaboration, synthesis, realization of concepts, and completion.The results of the work created 7 tapestries with the titles: Loyalty, Sensitivity, Courage, Grouping, Togetherness, Resilience, and Communicative. This final work is expected to be able to arouse the enthusiasm of the employees in creating tapestry works that are more interesting in the future.Kata kunci: semut, tapestri